Evaluation of the Nasopalatine Canal (NPC) in a subset of Pakistani population, using Cone Beam Computed Tomography (CBCT) - Khan, Madiha; Habib, Saqib; Ghafoor, Robia (Journal of the Pakistan Medical Association, 2022)
Objective: To evaluate variations in the shape, diameter, length and width of the nasopalatine canal along with the width of the buccal cortical bone anterior to it, using cone beam computed tomography imaging. Methods: The retrospective, cross-sectional study was conducted at the Aga Khan University Hospital, Karachi, from September to October 2020, and comprised pre-existing cone beam computed tomography scans taken between 2015 and 2020 of patients of either gender aged 18-60 years who had maxillary central incisors present. The shapes and dimensions of the nasopalatine canal were observed along with the buccal bone anterior to the nasopalatine canal. Data was compare with respect to age and gender. Data was analysed using SPSS 23. Results: Of the 90 scans evaluated, 46(51.1%) belonged to females with a mean age of 37.85+18.19 years, and 44(48.9%) belonged to males with a mean age of 38.07+13.58 years. The mean length and width of the nasopalatine canal was 11.28+1.90mm and 2.62+0.91mm, respectively. The nasopalatine canal was significantly longer (p<0.01) and wider (p=0.02) in males than females. The mean diameter of foramen of Stenson was 2.99+1.17mm and incisive foramen was 6.09+1.80mm. The mean width of the buccal cortical bone at the most coronal, middle and most incisal levels was 7.20+1.70mm, 6.12+1.31mm and 6.12+1.31mm, respectively. Buccal bone width was wider in males than females, but the difference was significant only at the midpoint (p<0.05). Conclusion: There was a significant difference in the dimensions of the width and length of the NPC with respect to gender. No significant differences were observed with respect to age. Key Words: Cone beam computed tomography, Nasopalatine canal, Pakistani population.